Strategy for Student Communication in Virtual Courses - Medina Cárdenas, Yurley; Bayona Ibáñez, Eduar; Rico Bautista, Dewar (Universidad Francisco de Paula Santander, 2024)
In online education, one of the most relevant concerns is meaningful learning from the application of new technologies for the acquisition and administration of knowledge autonomously by the student. Collaborative work has been incorporated into virtual courses to support learning, hence the importance of applying the appropriate strategies through a pedagogical method that manages to measure the level of knowledge construction. Using the right tools improves results. Efficient communication is a fundamental tool for conveying ideas and making decisions. In the digital environment, communication takes on multiple languages and forms, depending on the people who interact. In virtual courses, educational institutions have established a common language to facilitate interaction. Technologies in a virtual environment can significantly improve communication, as long as harmony and respect between the interlocutors are maintained. One of the advantages of Virtual Learning Environments (VLEs) is flexibility in terms of space and time, although it is necessary to follow a common prototype or language to ensure an effective flow of information and true communication. To achieve effective communication, the rules of virtual Netiquette, the TIGRE rubric and the Gunawardena model are deepened.